Serial image media for writing narrative text skills - Elisabeth Rosalinda Putri Lestari (Mitra Palupi, 2021)
Background: Using the media, the students are able to do proper sorting and treatment in learning activities. Purpose: This study aims to determine the effect of the application of serial image media on writing narrative text skills. Design and methods: This research uses a quantitative approach. The type used is a Quasi Experimental Design research, this design has a control group, but does not fully function to control the external variables that affect the implementation of the experiment. The research design used is the Non Equivalent Control Group Design. Results: The result showed that the experimental group obtained an average score of 82.86 and the control group obtained an average score of 71.18. the use of serial image media has a positive effect on writing narrative text skills of stu-dents in grade V Cipinang Besar Utara 7 Elementary school.